An overview of fused filament fabrication technology and the advancement in PLA-biocomposites - Samykano, Mahendran; Kumaresan, Rajan; Kananathan, Jeevendran; Kadirgama, Kumaran; Pandey, Adarsh Kumar (Springer Science and Business Media Deutschland GmbH, 2024)
The escalating significance of 3D printing in various industries is underscored by its ability to rapidly and cost-effectively produce distinctive parts. Among the 3D printing methods, fused filament fabrication (FFF) has emerged as a highly productive and cost-effective approach. While extensive efforts have been made to enhance the qualities of FFF products, challenges persist in material availability and quality compared to traditional methods. This study provides a meticulous overview of the FFF process, delving into various 3D printing processes, polymers, and polymer composites. Despite documented efforts to augment mechanical, thermal, and electrical properties, material constraints remain a focal point. Our analysis extends to various PLA/biocomposites, shedding light on achieved improvements and potential applications. Looking forward, the future trend in FFF technology suggests a paradigm shift towards enhanced material diversity and performance. Anticipated applications span beyond traditional use cases, encompassing sustainable manufacturing, medical devices, and eco-friendly construction materials. This comprehensive review not only consolidates the current state of FFF and PLA-biocomposites but also anticipates future trends and potential applications. This research enhances the current knowledge of additive manufacturing and sets a standard for assessing developments in FFF technology by comparing them to previous works.